2015
DOI: 10.18632/oncotarget.5735
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling identifies miR-31-5p/3p as associated with time to progression in wild-type RAS metastatic colorectal cancer treated with cetuximab

Abstract: The aim of our study was to investigate whether microRNAs (miRNAs) could serve as predictive biomarkers to anti-EGFR therapy (cetuximab, panitumumab) in patients with RAS wild-type (wt-RAS) metastatic colorectal cancer (mCRC). Historical cohort of 93 patients with mCRC (2006–2009) was included and further divided into exploratory and validation cohorts. MiRNAs expression profiling was performed on the exploratory cohort of 41 wt-KRAS mCRC patients treated with cetuximab to identify miRNAs associated with time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 16 publications
(20 reference statements)
2
53
0
Order By: Relevance
“…Numerous studies have shed light on tumor-targeting therapies using miRNAs as a novel diagnostic and therapeutic tools (7,8,12,25,28). In the present study, the downregulation of Klf4 and miR-31 was consistently observed in HCC tissues and they may thus serve as potential diagnostic markers and therapeutic targets for HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shed light on tumor-targeting therapies using miRNAs as a novel diagnostic and therapeutic tools (7,8,12,25,28). In the present study, the downregulation of Klf4 and miR-31 was consistently observed in HCC tissues and they may thus serve as potential diagnostic markers and therapeutic targets for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-31 has been found to be significantly overexpressed in colorectal cancer (12), squamous cell carcinoma of the tongue (13), head and neck squamous cell carcinoma (14), lung cancer (15) and esophageal squamous cell carcinoma (16); it has been found to be downregulated in bladder tumors (17), prostate carcinoma (18), gastric cancer (19), HCC (20), breast cancer (21) and serous ovarian carcinoma (22). Studies have suggested that Kruppel (or Krüppel)-like factor 4 (Klf4), a zinc-finger transcription factor, functions as a tumor suppressor or an oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them, for instance miR-221-5p (22), have been previously proposed as prognostic factors in other colorectal cancer studies. miR-331-3p has been linked to progression-free survival in patients with KRAS wild-type mCRC treated with anti-EGFR therapy in two independent studies (23, 24), and miR-497-5p has been involved in the regulation of the endogenous insulin-like growth factor receptor 1 expression, as well as cell survival, proliferation, and invasion (25). Our findings from the TCGA dataset substantiate their involvement in colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, microRNA-31 has been shown to activate RAS signaling by repressing RAS p21 GTPase activating protein 1 [44]. More evidence for the involvement of miR-31-3p in RAS signaling and EGFR inhibitor resistance came from a number of other studies, which make this microRNA a potential biomarker for future evaluation in prospective clinical trials [45,46,47,48]. Though we did not detect increased apoptosis activation in our cell models, there have been some reports about the pro-apoptotic effect of sorafenib in liver cancer in in vivo models [49].…”
Section: Discussionmentioning
confidence: 99%